Urinary levels of enniatin B and its phase I metabolites: First human pilot biomonitoring study. (August 2018) - Rodríguez-Carrasco, Yelko; Izzo, Luana; Gaspari, Anna; Graziani, Giulia; Mañes, Jordi; Ritieni, Alberto
Abstract: Enniatins (Enns) are mycotoxins produced by Fusarium spp. and are widely distributed contaminants of cereals and derivate products. Among the different identified enniatins, Enn B is the most relevant analogue in cereals in Europe. Therefore, the aim of this study was to investigate for the first time the occurrence of Enn B and Enn B phase I metabolites in 300 human urine samples throughout an ultrahigh-performance liquid chromatography-high resolution mass spectrometry (UHPLC-Q-Orbitrap HRMS) methodology. Three different sample preparation procedures were evaluated and salting-out liquid-liquid extraction showed satisfactory validation results. Enn B was quantified in 83.7% of samples ranging from 0.006 to 0.391 ng/mL (average content: 0.016 ng/mL). In line with the in vitro observations with human liver microsomes, in the here analyzed samples the Enn B monooxygenated, N -demethylated and dioxygenated metabolites were tentatively found in 87.7%, 96.3% and 6.7% of samples. The data of this pilot biomonitoring survey indicate a frequent intake of enniatins in Italy, supporting further toxicological studies to provide better basis for understanding their potential effects in humans. Highlights: UHPLC-HRMS method to determine enniatin B and its phase I metabolites in human urine was developed. Occurrence of Enn B and its metabolites were evaluated in 300 urine samples. Enn B phase I metabolites were investigated in human urine for the first time. Enn B was quantified in 83.7% of samples in a range from 0.006 to 0.391 ng/mL. Monooxygenated and N -demethylated species were the predominant Enn B metabolites.